Essays on Deleuze - Smith, Daniel W. (Daniel William), 1965- (Edinburgh University Press, 2012)
Combining his most important pieces over the last 15 years along with two completely new essays, 'On the Becoming of Concepts' and 'The Idea of the Open', this volume is Smith's definitive treatise on Deleuze. The four sections cover Deleuze's use of the history of philosophy, his philosophical system, several Deleuzian concepts and his position within contemporary philosophy. Smith's essays are frequent references for students and scholars working on Deleuze. Several of the articles have already become touchstones in the field, notably those on Alain Badiou and Jacques Derrida. For anyone interested in Deleuze's philosophy, this book is not to be missed.